Perancangan Sistem Informasi Kelayakan Bisnis untuk Mendukung Pengembangan Laboratorium Inkubator Bisnis - Mutinda Teguh Widayanto; Tamam Asrori; Mohammad Mohammad; Rizal Nurdin Imano; Naufal Abiyyu Imano (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet their failure rate remains high due to weak business planning and the absence of systematic feasibility studies. University business incubator laboratories are expected to assist prospective entrepreneurs in conducting comprehensive feasibility analyses, but evaluations are often performed manually and subjectively. This study aims to design a Business Feasibility Information System to support business incubator laboratories in achieving more objective, efficient, and documented assessments. The research employs a Research and Development (R&D) approach using the System Development Life Cycle (SDLC) model, encompassing stages of requirement analysis, system design, and conceptual validation. The system is designed to evaluate four key aspects of business feasibility: market, production, human resources, and finance. The result is a conceptual system prototype that integrates all aspects into a unified assessment framework. The findings indicate that the proposed system enhances the effectiveness of incubator laboratories in evaluating and assisting tenants objectively while fostering digital entrepreneurship literacy. The study implies that information technology integration is essential for strengthening MSME sustainability and decision-making in Indonesia.